Konsep Estetika Plato-Aristoteles & Implikasinya Pada Penilaian Sebuah Karya Seni - Dominica Diniafiat; Ambrosius M. Loho (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
The concept of classical aesthetics, with its central characters Plato and Aristotle, asserts that a work of art is the creations of a subject that is an imitation from the nature. Plato's concept is the process of creation, including the creation of works of art, as a process of imitation which he calls mimesis. Plato's opinion is based on their experience as figures of naturalism. While Aristotle is in the same line with Plato, who said that works of art are imitations, but for Aristotles, a work of art is not just an imitation, but the world of ideas, namely the forms of reality, only exists in nature. Between reality and ideas is a unity. The concept of these two classical philosophers about aesthetics is certainly important to considered for an assessment of various works of art. This article will discuss about how it is possible in the assessment of a work of art.